2010
DOI: 10.1111/j.1461-0248.2010.01548.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity and the stability of foodwebs

Abstract: Insect outbreaks in forest and agriculture monocultures led Charles Elton to propose, a half-century ago, that higher plant diversity stabilized animal foodweb dynamics in natural ecosystems. We tested this hypothesis by studying arthropod community dynamics in a long-term experimental manipulation of grassland plant species diversity. Over the course of a decade, we found that higher plant diversity increased the stability (i.e. lowered year-to-year variability) of a diverse (>700 species) arthropod community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
212
3
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(233 citation statements)
references
References 50 publications
(140 reference statements)
15
212
3
3
Order By: Relevance
“…Our finding supported that described by MacArthur (1955), where diversity at the prey level tended to stabilize the consumer population. Our results are also in line with previously published microcosm and field studies on the relationship of diversity, ecosystem functioning and stability in multitrophic systems (McGradySteed et al, 1997;Haddad et al, 2011) and suggest that diverse bacterial prey resources are a primary factor to make predator production more predictable.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding supported that described by MacArthur (1955), where diversity at the prey level tended to stabilize the consumer population. Our results are also in line with previously published microcosm and field studies on the relationship of diversity, ecosystem functioning and stability in multitrophic systems (McGradySteed et al, 1997;Haddad et al, 2011) and suggest that diverse bacterial prey resources are a primary factor to make predator production more predictable.…”
Section: Discussionsupporting
confidence: 93%
“…Stability relies on interacting species and trophic interactions including the extent of predator feeding specialization and prey-predator connectivity (McCann, 2000;Haddad et al, 2011). We measured stability as the variability in predator production by using the CV, where high values exhibit low ecosystem reliability (Haddad et al, 2011;Leary et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This richness effect was observed irrespective of bacterial identities and top-down control by predators. Functional stability of environmental processes is a fundamental ecosystem parameter [45,46], with high C.V. reflecting low ecosystem reliability [12,47]. Our results are consistent with earlier findings showing that speciesrich ecosystems tend to use resources more efficiently [48] and that ecosystem processes stabilize with higher richness [49].…”
Section: Discussionsupporting
confidence: 91%
“…[1 ,2-8,9 ]). Studies have found that plant diversity positively influences arthropod diversity and abundance [3,4,8,10], and alters plant-arthropod and arthropod-arthropod interactions [3,7,11,12]. These findings emphasize that conserving and manipulating plant diversity in natural and managed systems, respectively, is crucial for maintaining ecosystem function [13][14][15].…”
Section: Introductionmentioning
confidence: 95%